Implementasi Diskusi Dan Presentasi Untuk Meningkatkan Self-Confidence Siswa Pada Mata Pelajaran PAI Dan BP - Rianto, Nofri; Asri, Zainal; Zalnur, Muhammad; Gusnetti, Gusnetti; Reflianto, Reflianto (Institut Agama Islam Sumatera Barat, 2024)
This study aims to explore the forms of planning, implementation, and the factors influencing the execution of discussion and presentation methods in Islamic Education (PAI) and Character Education (BP) at SMKN 2 Pariaman. The research employs a qualitative approach with descriptive methods, involving observations and interviews. The findings reveal that the planning of discussion and presentation methods utilizes various learning media, such as the internet, infocus projectors, audio systems, laptops, mobile phones, and PowerPoint, to convey material about hard work. The implementation of this method involves motivation from educators, development of students' talents and interests through organizational activities, and creating a supportive environment for less confident students. Furthermore, the study identifies factors affecting the implementation of these methods, including family, economic, environmental, and physical factors of the students. Efforts to address these challenges include public speaking training, participation in extracurricular activities, and guidance from educators, particularly from counseling services. The findings indicate that the discussion and presentation methods are not only effective in delivering content but also contribute to the development of competencies and learning interests of students at SMKN 2 Pariaman.